LANGKAH PENELITIAN PENDIDIKAN: PENEMUAN MASALAH, TELAAH PUSTAKA, PERSIAPAN PENELITIAN, PENGUMPULAN DATA, ANALISIS DATA DAN PENYIMPULAN/PEMAKNAAN, DAN PELAPORAN & EVALUASI PENELITIAN - Ardian; Dina Hermina; Salamah (PT. Saha Kreasi Indonesia, 2026)
Research is a systematic and structured scientific process aimed at finding solutions to various problems, particularly in the field of Islamic education. This paper aims to describe the steps of educational research, including problem identification, literature review, research preparation, data collection, data analysis, conclusions, and research reporting and evaluation. The method used in writing this paper is a literature study, reviewing various relevant literature sources. The results of the discussion indicate that the research begins with the identification and formulation of a clear problem as the primary basis for the research. Next, a literature review is conducted to obtain a strong theoretical foundation. The research preparation stage includes planning the research methodology and instruments. Data collection is conducted systematically according to the method used, then analyzed to produce valid and objective findings. The final stage includes the conclusion of the research results, as well as reporting and evaluation as a form of scientific accountability. By following systematic research stages, educational research is expected to produce findings that are relevant, valid, and beneficial for the development of science and improving the quality of Islamic education practices.